Clinical profile and mortality predictors for tuberculosis disease among patients with solid tumours. Issue 11 (2nd November 2022) - Lira, Camila Agra Gomes de; Peixoto Bittencourt, Driele; Bicalho, Camila da Silva; Bonazzi Rodrigues, Patrícia; Freire, Maristela Pinheiro; Abdala, Edson; Pierrotti, Lígia Camera
Abstract: Background: The characteristics of Mycobacterium tuberculosis (MTb) disease are still obscure in patients with solid tumours, as well as the benefits of screening and treating latent tuberculosis infection (LTBI) in these patients. Our objective was to trace the clinical profile of these individuals and assess the mortality predictors related to tuberculosis (TB). Methods: We reviewed the medical records of 126 patients with solid tumours malignancy and who developed TB disease between January 2009 and April 2018 at a cancer referral centre. Results: The most common locations of malignancy were head and neck, with squamous cell carcinoma being the most frequent histological type, the majority (97/126) presenting locally invasive tumours (T3 or T4). A total of 120 had TB pulmonary and the microbiological diagnosis was performed in 103/126. The following variables were associated with the risk of death from TB: DPOC lung cancer, BMI, malnutrition, metastasis and ECOG 3 or 4. Previous chemotherapy treatment was a protective factor. Conclusions: Male, usage of alcohol and smoking were the most predominant patients characteristics in our sample. In the multivariate analysis, lung cancer, presence of metastasis and ECOG ≥ 3 were associated with death from TB.